Surviving the challenges of micro lending in a hyperinflationary environment: Zimbabwean case - Chikoko, Laurine; Kwenda, Farai (Academy of Business & Scientific Research, 2016)
This study reviews the survival strategies of micro lending institutions in dealing with the challenges given the hyperinflationary environment Zimbabwe went through over the period 1999 - 2008. The microfinance sector in Zimbabwe was still in its infancy and had numerous challenges. Hyperinflation exacerbates the situations with a lot of these institutions' survival under serious threat. Some of the challenges that confronted micro lending institutions include product pricing; high delinquency levels and capital erosion. Micro lending institutions adopted a number of survival strategies which include; cost cutting, client rating and retention, product development, streamlining operations among others. Though constrained by the regulatory framework and capacity challenges, some of the survival strategies prescribed here is that necessity is the mother of innovation and every crisis presents hidden opportunities and no matter the challenge, there is a way of escape.